The impact of maternal vitamin D deficiency on fetal development and long-term health outcomes in offspring - Kaczmarek , Aleksandra; Kaczmarek , Wojciech; Krakowiak, Magdalena; Gołacki, Rafał; Jabłonowska, Magdalena; Bagiński, Konrad; Jurczuk, Aleksandra; Bałdyga, Paulina; Wilczyńska, Aleksandra; Depta, Piotr (Quality in Sport, 2025)
Introduction: Vitamin D is a vital micronutrient that supports mineral balance, modulates immune activity, and contributes to healthy fetal development. Adequate maternal vitamin D levels are essential for proper placental function and optimal intrauterine growth. Nevertheless, deficiency of this nutrient remains common among pregnant women worldwide, posing potential risks for both maternal and child health [1]. The purpose of this review is to critically evaluate current evidence regarding the influence of maternal vitamin D insufficiency on fetal growth, perinatal outcomes, and the longer-term health of offspring — particularly its implications for skeletal integrity, immune system maturation, metabolic regulation, and neurodevelopment. Materials and methods: Literature from 2015–2025 was systematically searched through PubMed, Scopus, and Google Scholar using the terms: “thoracic outlet syndrome,” “overhead athletes,” “Paget-Schroetter syndrome,” “effort thrombosis,” “vascular compression,” and “rehabilitation.” Priority was given to systematic reviews, clinical trials, and high-quality case studies Summary: Evidence suggests that low maternal vitamin D levels are associated with impaired fetal bone mineralization, increased risk of preeclampsia and preterm birth, and lower birth weight. Beyond the neonatal period, maternal deficiency has been linked to higher susceptibility to respiratory infections, allergic and autoimmune diseases, insulin resistance, and neurodevelopmental disorders in children. Conclusions: Insufficient maternal vitamin D levels constitute a modifiable determinant that may influence offspring health well beyond the perinatal period. Ensuring adequate vitamin D status during pregnancy—through targeted supplementation programs and evidence-based public health initiatives—can contribute to improved maternal and neonatal outcomes and may help lower the risk of chronic diseases later in life.